How to read a book : a classic guide to intelligent reading - Adler, Mortimer Jerome, 1902-2001.; Van Doren, Charles, 1926- (New York : Simon and Schuster, 1972)
Investigates the art of reading by examining each aspect. Includes discussion of issues that may be encountered, and offers suggestions on how to overcome them.
The dimensions of reading. The activity and art of reading ; The levels of reading ; The first level of reading : elementary reading ; The second level of reading : inspectional reading ; How to be a demanding reader -- The third level of reading : analytical reading. Pigeonholing a book ; X-raying a book ; Coming to terms with an author ; Determining an author's message ; Criticizing a book fairly ; Agreeing or disagreeing with an author ; Aids to reading -- Approaches to different kinds of reading matter.
Bibliography: p. 347-362.
Keywords: Reading; Nonfiction